Transcriptome-based network analysis reveals a spectrum model of human macrophage activation - Xue, Jia; Schmidt, Susanne V.; Sander, Jil; Draffehn, Astrid; Krebs, Wolfgang; Quester, Inga; De Nardo, Dominic; Gohel, Trupti D.; Emde-Rajaratnam, Martina; Schmidleithner, Lisa; Ganesan, Hariharasudan; Nino-Castro, Andrea; et al. (Immunity, 2014)
Macrophage activation is associated with profound transcriptional reprogramming. Although much progress has been made in the understanding of macrophage activation, polarization, and function, the transcriptional programs regulating these processes remain poorly characterized. We stimulated human macrophages with diverse activation signals, acquiring a data set of 299 macrophage transcriptomes. Analysis of this data set revealed a spectrum of macrophage activation states extending the current M1 versus M2-polarization model. Network analyses identified central transcriptional regulators associated with all macrophage activation complemented by regulators related to stimulus-specific programs. Applying these transcriptional programs to human alveolar macrophages from smokers and patients with chronic obstructive pulmonary disease (COPD) revealed an unexpected loss of inflammatory signatures in COPD patients. Finally, by integrating murine data from the ImmGen project we propose a refined, activation-independent core signature for human and murine macrophages. This resource serves as a framework for future research into regulation of macrophage activation in health and disease.
Gesehen am 07.08.2024